Pregnancy, childbirth and neonatal outcomes associated with adolescent pregnancy - Amene Ranjbar; Maliheh Shirzadfard Jahromi; Banafsheh Boujarzadeh; Nasibeh Roozbeh; Vahid Mehrnoush; Fatemeh Darsareh (BMJ Publishing Group, 2023)
Objective: To assess the obstetric and neonatal outcomes associated with adolescent pregnancy in Iran. Methods: We retrospectively assessed women who gave birth between January 1st, 2020, and January 1st, 2022. These pregnant women were separated into two groups: (1) women aged 19 and younger; (2) women aged 20-34 years. Main outcome measures include preterm birth, maternal comorbidities, preeclampsia, eclampsia, low birth weight (LBW), intrauterine growth restriction (IUGR), placenta abnormalities, placenta abruption, chorioamnionitis, meconium fluid, fetal distress, methods of delivery, rate of cesarean section (CS), perineal lacerations, postpartum hemorrhage, childbirth trauma, shoulder dystocia, congenital malformation, and unfavorable maternal and neonatal outcome. Logistic regression models were used to determine the influence of teenage pregnancy on adverse pregnancy and childbirth outcomes. Results: Of 7033 deliveries, 92.4% of women were adults, and 7.6% were adolescents. Adolescents residing in rural districts were more common than adults (42.3% vs. 33.7%). However, access to prenatal facility care was the same as the majority of women had 6-10 prenatal care visits during their pregnancy. There was no difference in the risk of preeclampsia, placenta abruption, placenta previa, fetal distress, preterm labor, shoulder dystocia, perineal lacerations, childbirth trauma, congenital malformation, postpartum hemorrhage, intensive care unit admission, maternal death, and unfavorable neonatal outcome including stillbirth, neonatal intensive care unit admission, neonatal death in adolescent pregnancies compared to adults. Adolescents had a significantly higher risk of LBW (OR: 1.47, 95%CI: 1.01-2.73), IUGR (OR: 1.96, 95%CI: 1.31-2.45), and meconium fluid (OR: 1.74, 95%CI: 1.41-2.32), however, there was no statistically significant difference after adjusting the confounding factors. Compared with adults, adolescents had a significantly lower risk of CS (aRR: 0.67, 95%CI: 0.51-0.77) and a lower risk of gestational diabetes (aRR: 0.78, 95%CI: 0.51-0.95). Conclusions: Although we found no serious consequences of adolescent pregnancy, more research is needed to reach a more accurate conclusion about teenage pregnancy.